Análise da maturidade do processo de armazenagem em centros de distribuição de supermercados em Fortaleza/CE: um estudo multicasos - Jesus, Piter Anderson Severino de (2014)
Logistics and processes, especially the storage, are presented as one of the ways that the company has to reduce costs and add value to stakeholders. This research aims to develop a method for analyzing the maturity to analyze the process of storage of Distribution Centers (DC) in Fortaleza / CE. It is understood by the maturity as the CD is evolved in a particular area or process. Through this analysis, the Distribution Centre can leverage the strengths and resolve or mitigate those weaknesses. To this end, attributes, dimensions and practices for infrastructure organization, people and technology, as well as its internal and external interfaces were established. The instrument for the diagnosis of CD For the elaboration of the method of maturity assessment was also prepared, library research and validation were performed with professional logistics. The tool was applied to Distribution Centres to supermarkets in order to analyze the maturity of the storage of CDs Thus, the degree of maturity of the process can be analyzed and proposals are ways to improve it. After application of the instrument can observe the heterogeneity of the surveyed companies, as well as the need for improvements in communication with suppliers.